Appearance Of Production Of Super Age Kampung Chicken 1-7 Weeks Using Rations Containing Tofu Pulp - Hasmirawati, Hasmirawati; Aka, Rahim; Nuraini, Nuraini (Pascasarjana Universitas Sulawesi Tenggara, 2021)
The study aims to find out the appearance of super kampung chicken production aged 1-7 weeks at the giving of different levels of tofu pulp in rations. held in January-March in the Laboratory of Livestock Production Science and Technology Poultry Livestock Unit Faculty of Animal Husbandry Halu Oleo University. Using 64 super kampung chickens, using a Complete Random Plan (RAL) 4 treatments namely P0 (0% tofu pulp flour), P1 (5% tofu pulp flour), P2 (10% tofu pulp flour) P3 (15% tofu pulp flour) and 4 repeats. Research variables are ration consumption, weight gain, ration conversion analyzed using fingerprints followed by the Smallest Real Difference test (BNT). The results of the analysis of average consumption of rations (g/tail/day) 37.12(P0), 36.15(P1), 36.70 (P2), 34.23 (P3). Average Weight Gain (g/tail/day) 13.05 (P0), 11.81 (P1), 11.74 (P2), 10.58(P3). Ration conversion average 2.71 (P0), 3.07 (P1), 3.16 (P2), 3.24(P3). The results of the study showed that the provision of tofu pulp flour has no real effect (P>0.05) on the consumption of super kampung chicken rations, while in the weight gain of flour giving tofu pulp has a very real effect (P<0.01) and a real effect (P<0.05) on the conversion of super kampung chicken rations.